Dowry Prohibition Act, 1961 - Professional Book Publication (Delhi: Professional Book Publication, 2023)
Dowry Prohibition Act, 1961 as amended by The Jammu and Kashmir Reorganisation Act, 2019
Keywords: The Jammu and Kashmir Reorganisation Act, 2019; Bare Act